ORDER OF CONFIRMATION OF THE COUNTRY OF GOODS' ORIGIN IN CONTRACTUAL SYSTEM - E. V. Shikalova (Модернизация, инновация, развитие, 2015)
The current legislation about public procurements provides cases of obligatory confirmation of the country of goods' origin, however the order and methods of its confirmation in practice remain debatable.